Inducement of an Anisotropic One‐dimensional Surface of Solution‐derived Indium Gallium Oxide Film via Imprint Lithography for Liquid Crystal Alignment. Issue 12 (10th November 2022) - Lee, Dong Wook; Kim, Eun Mi; Heo, Gi Seok; Kim, Dong Hyun; Oh, Jin Young; Yang, Da Bin; Jang, Jong In; Jeong, Hae‐Chang; Seo, Dae‐Shik
Abstract: This study uses imprint lithography to produce an anisotropic unidirectional indium gallium oxide (IGO) film for the uniform liquid crystal (LC) alignment layer. The curing temperature was controlled to 110, 180, and 250 °C during the process, and the 250 °C cured film presented a distinct one‐dimensional pattern transferred from the polydimethylsiloxane (PDMS) mold during scanning electron microscopy (SEM). X‐ray photoelectron spectroscopy (XPS) confirmed an active thermal oxidation effect at a high curing temperature, contributing to the formation of a unidirectional structure. This unidirectional IGO structure functioned as a guide for LCs and induced a uniform alignment state, verified by polarized optical microscopy (POM) and a pre‐tilt angle analysis. The IGO film also revealed improved thermal endurance to the LC alignment state and optical transmittance compared with the conventional rubbed polyimide (PI) layer. Given this performance, the one‐dimensional pattern‐imprinted IGO film can be a promising LC alignment layer for an advanced LC system. Abstract : A uniform and homogeneous liquid crystal (LC) alignment with high optical transparency is achieved by an imprinting lithography method. A InGaO film is used as the LC alignment layer, and the imprinted film represents the anisotropic unidirectional surface which derives LC orientation. The alignment layer also shows an excellent thermal budget suitable for LC systems.